Morphological Profile of Ovarian Tumours - Bilquis Begum, Iram Nadeem Rana, Nadeem Ikram (Journal of Rawalpindi Medical College, 2016)
Background: To study the morphological types of ovarian tumours . Methods: In this descriptive, cross sectional study all consecutive specimens of ovarian tumours . Gross examination was done, representative sections taken, processed and paraffin embedded blocks made. Sections of blocks were taken by microtome and the prepared slides were stained by H&E stain and examined under the microscope. Results obtained were analyzed according to age and tumour type. Results: A total of 182 cases of ovarian neoplastic lesions were reported, out of which 67.6% were benign while 32.4% were malignant tumours. Surface epithelial tumours were the commonest and constituted 49.2 % followed by germ cell tumours 20.3 %, sex cord stromal tumours 18.6 % and metastatic tumours 11.9 %. Mucinous tumours were more common than serous tumours. Among the benign category, mature cystic teratoma was the commonest.Benign tumours were more common in young females while incidence of malignant tumours increased with the advancing age. Conclusion: Benign ovarian tumours are more common than malignant ovarian tumours. Among the surface epithelial tumours, mucinous tumours are the commonest in our study followed by germ cell tumours. Recognition of border line tumours is very important because such patients need close follow up.